Biannual public budget: a strategy for administrative efficiency (2018)
Based on the experience evidenced in the national territory, the principle of budgetary annuity is not efficient in the Colombian system, because it conflicts with the estimated deadlines in the contractual regulations and doesn ́t adjust to the real situations, that ́s the reason why the extension of this principle to the plurianualidad will allow to strengthen and consolidate the territorial decentralization, materializing the constitutional objective of reinforcing the decentralization through effective mechanisms that make it possible, and ensuring that the resources of the territorial entities will be invested in the execution of projects that contribute to regional development, that is, that investment that produces impacts. Thus, the multi-annual budget constitutes a solution to the current problems of inefficiency in the execution of the budget, evidenced in the territorial entities in Colombia.